Феномен поліцейської культури (police culture) у сучасних зарубіжних дослідженнях - Ламаш, І. В.; Lamash, I. V.; ORCID: http://orcid.org/0000-0002-9548-4006; ResearcherID: I-7320-2016 (Право і Безпека. - 2016. - № 2 (61). - С. 11–17, 2016)
Подано огляд сучасних зарубіжних досліджень феномена поліцейської культури (police culture), розглянуто його зміст у контексті поліцейської науки (police science). Представлено дослідження науковців Великобританії, Китаю, Нідерландів, Норвегії, Сполучених Штатів Америки, Швеції, Франції, предметом яких є зміст і специфіка police culture, а також такі її аспекти, як професійна ідентичність, професійна соціалізація, сприйняття поліцейськими їх ролі та ставлення до норм, обумовлених організаційною культурою, вплив вищої освіти та роль storytelling у формуванні поліцейської культури.

The article presents an overview of current foreign studies of the phenomenon of police culture. The content of this phenomenon in the context of police science is considered. Noticed, that in last decades, for the most part, studies of police culture have focused rather narrowly on Anglo-American state policing forms but in recent years police culture has received increased attention in a broader geographical and terminological context. There were presented studies of researchers from Great Britain, China, Netherlands, Norway, United States of America, Sweden, France, the subject of which is the content and specificity of police culture, as well as such aspects of it as a professional identity, pre-professional and professional socialization, the perception of police officers of their role ofcrime fighting and community service and attitudes to the norms, due to the organizational culture, the effect of higher education on police culture and the role of storytelling (like a part of canteen culture) in the formation of the police culture. The review leads to the conclusion that there is a direct connection between police work and a unique occupational culture. In the terms of cultural psychology, police culture on the one hand is the culture of the high context in which human behavior is determined by the context of the situation, but individual manifestations of the personality has not particular significance. The requirements of this type of culture allow (and force) the person to behave and express thoughts and feelings in accordance with the situation and environment. On the other hand, police culture can be attributed to the culture of low-context, in which is particularly important stability and consistency of a certain set of personality manifestations in different contexts, regardless of external factors. In this sense, a policeman acts as an indigenous personality with a set of special traits and characteristics which are unique to that culture. The nature of the policing role has created a culture specific to this function. Like any organizational culture, police culture consists of widely shared attitudes, values and norms. The review of the studies evidence on the updating of interest of researchers to this problem in the context of changes in police culture on a global scale, expanding the field of phenomenological research and confirms the need to use foreign experience in the practice of the reform of internal affairs agencies in Ukraine.

Представлен обзор современных зарубежных исследований феномена полицейской культуры (police culture), рассмотрено его содержание в контексте полицейской науки (police science). Представлены исследования учёных Великобритании, Китая, Нидерландов, Норвегии, Соединенных Штатов Америки, Швеции, Франции, предметом которых является содержание и специфика police culture, а также такие её аспекты, как профессиональная идентичность, профессиональная социализация, восприятие полицейскими их роли и отношение к нормам, обусловленным организационной культурой, влияние высшего образования и роль storytelling в формировании полицейской культуры.
Phenomenon of police culture in current foreign studies
Феномен полицейской культуры (police culture) в современных зарубежных исследованиях
Ламаш, І. В. Феномен поліцейської культури (police culture) у сучасних зарубіжних дослідженнях / І. В. Ламаш // Право і Безпека. - 2016. - № 2. - С. 11-17.
Ламаш І. В. "Феномен поліцейської культури (police culture) у сучасних зарубіжних дослідженнях." Право і Безпека 2 (2016): 11-17.
Lamash, I.V. (2016), “Phenomenon of police culture in current foreign studies” [“Fenomen politseiskoi kultury (police culture) u suchasnykh zarubizhnykh doslidzhenniakh”], Pravo i Bezpeka, No. 2, pp. 11–17.
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; організаційна культура; поліцейська культура; поліцейські науки; професійна ідентичність; професійна соціалізація; зарубіжний досвід; зарубіжні країни; organizational culture; police culture; police science; professional identity; professional socialization; зарубежный опыт; foreign experience; организационная культура; полицейская культура; полицейские науки; профессиональная идентичность; профессиональная социализация